Assessing the Alignment of Zakat Allocation with the Sustainable Development Goals: An Empirical Analysis of Poverty and Education Outcomes - Maghfirah, Maghfirah; Maulidizen, Ahmad; Rizapoor, Habiburrahman (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Zakat plays a strategic role in Islamic social finance as an instrument for poverty alleviation and social welfare; however, its contemporary distribution practices often remain concentrated on short-term charitable relief rather than long-term socio-economic empowerment, raising questions about its alignment with the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 4 (Quality Education). This study aims to examine conceptually the alignment between zakat allocation and selected SDG targets and to develop a normative impact assessment framework grounded in sharia objectives that reorients zakat evaluation toward sustainable empowerment outcomes. Using a qualitative-descriptive method based on a systematic literature review, the study synthesizes classical Islamic jurisprudential principles with contemporary development and Islamic social finance scholarship to critically assess prevailing zakat governance models. The findings indicate that zakat institutions predominantly rely on output-based indicators—such as the volume of funds distributed and the number of beneficiaries—while insufficiently addressing outcome-based dimensions related to economic independence, educational advancement, and social empowerment. In response, the article proposes an SDGs-oriented, capability-based assessment framework structured around three interrelated dimensions: economic capability, educational capability, and social empowerment capability. The study recommends integrating long-term capability indicators into zakat governance, strengthening outcome-focused monitoring systems, and redesigning allocation strategies to prioritize sustainable human development, thereby repositioning zakat as a transformative mechanism consistent with both sharia objectives and global development objectives.